The unlikely pilgrimage of Harold Fry - Joyce, Rachel (London : Black Swan., 2013)
Harold Fry is convinced that he must deliver a letter to an old love in order to save her, meeting various characters along the way and reminiscing about the events of his past and people he has known, as he tries to find peace and acceptance.
Booklist starred
Kirkus Review
Library Journal
Booklist starred, June 2012
Kirkus Review, June 2012
Library Journal, June 2012
Keywords: Men -- Great Britain -- Fiction; Walking -- Fiction; Men -- Great Britain -- Fiction; Walking -- Fiction; Great Britain -- Fiction; Great Britain -- Fiction